Implementasi Kebijakan Kepala Sekolah dalam Mendorong Pembelajaran Inovatif: Studi Kasus di Sekolah Dasar - Winda Juniarsih; Fatimah Yuliani; Siti Halimah; Dr Darsinah; Dr Wafrotur Rohmah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of school principal policies in promoting innovative learning in elementary schools. The research is grounded in the need for 21st-century learning, which emphasizes critical thinking, creativity, collaboration, and communication. A qualitative approach with a case study design was employed at SD Muhammadiyah 19 Kemlayan. The participants included the principal, teachers, and students selected through purposive sampling. Data were collected through interviews, observations, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that the principal implemented policies through teacher professional development, technology integration, and the establishment of a collaborative school culture. These strategies positively influenced student engagement and the use of innovative teaching methods. However, challenges such as limited teacher competence, resistance to change, and inadequate facilities were identified. This study concludes that effective principal leadership plays a crucial role in fostering innovative learning in elementary education.